MONOTONICITY AND EXTREMA OF FUNCTIONS - Boboqulova Durdona Sanjar qizi (INTEGRATION OF EDUCATION AND SCIENCE: GLOBAL CHALLENGES AND SOLUTIONS, 2025)
Abstract: This paper explores the mathematical concepts of monotonicity and extrema of real-valued functions. These characteristics play a crucial role in the study of calculus, optimization, and mathematical modeling. The article introduces formal definitions, analytical tools such as derivatives to determine increasing or decreasing behavior, and conditions for identifying local and global extrema. Practical applications in economics, physics, and engineering are also discussed.